Melhora da regeneração óssea e cartilaginosa com uso de células-tronco mesenquimais em pacientes com fratura óssea ou osteoartrite - Tura, Bethânia Borges (2022)
Tissue engineering is an area that comes as an alternative to compensate for the shortage of organs for transplantation and mesenchymal stem cells come as an alternative for the reconstruction of new tissues. Mesenchymal stem cells have been an alternative in the fracture repair process and in the reconstruction of articular cartilage. The objective of this work is to analyze the literature and develop a systematic review on the use of mesenchymal stem cells in the treatment of patients who presented bone fractures or osteoarthritis. The systematic review protocol was designed according to the Cochrane Handbook for Systematic Reviews of Interventions, the PICO question to be answered: "Is there improvement in bone and cartilage regeneration with the use of mesenchymal stem cells in patients with bone fracture or osteoarthritis? ". Searches were performed in the following databases: US National Library of Medicine (Pubmed / MEDLINE), Excerpta Medica Database (EMBASE), Scientific Electronic Library Online (SCIELO), VHL (LILACS) and Cochrane Controlled Trials Database. The screening of titles and abstracts was performed by two researchers and disagreements were arbitrated by a third evaluator. The research resulted in six articles and demonstrated that the use of mesenchymal stem cells is efficient in fracture repair and cartilage regeneration in patients with osteoarthritis. However, the number of studies in humans is still limited. Therefore, we suggest conducting more randomized studies involving a larger number of treated patients with long-term follow-up.